STUDI KUALITAS LINGKUNGAN PERAIRAN DI DAERAH BUDIDAYA PERIKANAN LAUT DI TELUK KAPING DAN TELUK PEGAMETAN, BALI - Slamet, Bejo; Arthana, I Wayan; Budiarsa Suyasa, I W. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 3 No 1)
The purpose of this study was to know the coastal environmental quality of Kaping and Pegametan Bay coastal area. The study was conducted from 14 stations with 3 replicates of water sampling and 5 replicates of makrozoobenthos sampling. The result showed that water quality namely TSS, DO, NH3 and BOD5 were still in line criterion stated by office of KLH (2004). About 49 species of makrozoobenthos were examined, with abundance of makrozoobenthos was 58-209 ind./ 1,125 cm2 and diversity indeks was 1,56-2,91. The result on the integrated water quality analyses showed that the water quality all of station was classified to light pollution. This result showed that the enviromnental of Kaping Bay dan Pegametan Bay coastal area was competent for mariculture although lower compered with control. For the continuity of fisheries aquaculture in Kaping Bay dan Pegametan Bay, Long term effort in environment conservation is needed better stretegy and action in an integrated and sustainable manners.
Keywords: environmental quality, mari culture area.